2019
DOI: 10.1021/acs.biochem.8b01101
|View full text |Cite
|
Sign up to set email alerts
|

Dihedral Angle Calculations To Elucidate the Folding of Peptides through Its Main Mechanical Forces

Abstract: This study reports a general method to calculate dihedral angles (φ and ψ) of a given amino acid sequence, focusing on potential energy and torque moment concepts. By defining these physical measures in relation to the chemical interactions that occur on each single amino acid residue within a peptide, the folding process is analysed as the result of main mechanical forces (MMF) exerted in the specific amino acid chain of interest. As a proof of concept, Leu-enkephalin was initially used as a model peptide to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This study is focused on the chemical interactions developed amongst the side chains of the residues and these were considered to be the informations required to fold the polypeptide. The survey shows a good agreement between the calculated and the experimentally determined values, thus the method presented, combined to the previous [6] , reveals to be an efficient approach to predict at least the backbone dihedral angles φ starting from the amino acid sequence.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…This study is focused on the chemical interactions developed amongst the side chains of the residues and these were considered to be the informations required to fold the polypeptide. The survey shows a good agreement between the calculated and the experimentally determined values, thus the method presented, combined to the previous [6] , reveals to be an efficient approach to predict at least the backbone dihedral angles φ starting from the amino acid sequence.…”
Section: Introductionsupporting
confidence: 54%
“…The chemical interactions among the side chains of the amino acid residues were supposed to be the informations required to fold the polypeptide: these allow the development of mechanical forces which induce the twistings necessary to fold the polypeptide. This approach, already reported in literature [6] and deepen in this study, showed that it is possible to calculate the backbone dihedral angles φ starting from the amino acid are wrong. The method thus, aims to be a useful tool to investigate partially the structure of a polypeptide chain (since concerns only φ), predicting it starting from the amino acid sequence.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations